Internet content regulation: contemporary legal and regulatory issues in the changing digital landscape - Daud, Mahyuddin (IIUM Press, 2019)
Internet content regulation : Contemporary legal and regulatory issues in the changing digital landscape is written as a reference book for legal and ICT researchers, policy makers, practitioners, academics and students that deepen their understandings on how Internet content may be regulated.